We have the injury prevention exercise programme, but how well do youth follow it? - Perera, N. P. P.; Hägglund, M. (Journal of Science and Medicine in Sport, 2020)
Objectives: Describe the exercise fidelity and utilisation fidelity of the Knee Control injury prevention exercise programme (IPEP) in youth floorball alongside an intervention RCT.